Osteoarthritic Milieu Affects Adipose‐Derived Mesenchymal Stromal Cells. Issue 2 (30th August 2019) - Manferdini, Cristina; Paolella, Francesca; Gabusi, Elena; Cattini, Luca; Rojewski, Markus; Schrezenmeier, Hubert; Addimanda, Olga; Meliconi, Riccardo; Lisignoli, Gina
Abstract : The objective of this study was to define in vitro the effects of osteoarthritic (OA) milieu and hypoxia on good manufactured practice‐adipose‐derived mesenchymal stromal cells (GMP‐ASC) that are commonly utilized in cell therapies. Hypoxia increased GMP‐ASC proliferation. OA milieu‐treated GMP‐ASC showed an increase in cellular migration, as well as in CXCR3, CCR3, and IL6R and a decrease in CCR1 and CCR2 receptors in hypoxia. CXCL10/IP10 was the only chemokine of the OA milieu down‐modulated after treatment with GMP‐ASC. ABSTRACT: The objective of this study was to define the effects of osteoarthritic (OA) milieu on good manufactured practice‐adipose‐derived mesenchymal stromal cells (GMP‐ASC) that are commonly utilized in cell therapies. Two different OA milieu: OA synovial fluid (SF) and OA‐conditioned medium (CM) from synoviocytes were used to treat GMP‐ASC both in normoxia or hypoxia. GMP‐ASC were tested for cell migration, proliferation, cytokine receptors expression (CXCR1, CXCR2, CXCR3, CXCR4, CXCR7, CCR1, CCR2, CCR3, CCR5, IL6R), and cytokines (CXCL8/IL8, CXCL10/IP10, CXCL12/SDF‐1, CCL2/MCP1, CCL3/MIP1α, CCL4/MIP1β, CCL5/RANTES, IL6) release. Healthy SF was used as controls. We demonstrated that GMP‐ASC show an increase in proliferation, migration, and modulation of CXCR1, CXCR3, CCR1, and CCR5 receptors in hypoxic condition. Moreover, GMP‐ASC migration increased 15‐fold when treated either with OA‐SF or OA‐CM compared with healthy SF both in normoxia and hypoxia. GMP‐ASC treated in both OA milieu showed an increase in CXCR3, CCR3, and IL6R and a decrease in CCR1 and CCR2 receptors. In OA‐SF, we detected higher amount of CXCL10/IP10 than in OA‐CM, while CCL2/MCP1 and CCL4/MIP1β were higher in OA‐CM compared with OA‐SF. CXCL10/IP10 was the only chemokine of the OA milieu, which was down‐modulated after treatment with GMP‐ASC. In conclusion, we demonstrated specific effects of OA milieu on both GMP‐ASC proliferation, migration, and cytokine receptor expression that were strictly dependent on the inflammatory and hypoxic environment. The use of characterized OA milieu is crucial to define the therapeutic effect of GMP‐ASC and indicates that CXCL10/IP10–CXCR3 axis is partially involved in the GMP‐ASC effect on synovial macrophages. © 2019 The Authors. Journal of Orthopaedic Research ® published by Wiley Periodicals, Inc. on behalf of Orthopaedic Research Society. J Orthop Res 38:336‐347, 2020